2022
DOI: 10.1186/s40634-021-00443-x
|View full text |Cite
|
Sign up to set email alerts
|

Common peroneal nerve palsy after TKA in valgus deformities; a systematic review

Abstract: Purpose The aim of this systematic review is to investigate the prevalence of Common Peroneal Nerve Palsy after total knee arthroplasty in valgus deformities. Furthermore, the effectiveness of a peroneal nerve release prior to arthroplasty to prevent the palsy will be investigated. Methods PubMed and Google Scholar were searched. Search terms regarding valgus deformity and total knee arthroplasty were used. Data analysis and extraction were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Due to the limited number of studies investigating FNR, no consensus has yet been reached on the value and indication of the procedure. A systematic review demonstrated no significant differences in FNP rate between valgus TKA with and without FNR (2.4% vs 2.1%) [18]. Therefore, the authors of this chapter do not recommend the routine use of FNR.…”
Section: The Fibular Nerve Dilemmamentioning
confidence: 85%
“…Due to the limited number of studies investigating FNR, no consensus has yet been reached on the value and indication of the procedure. A systematic review demonstrated no significant differences in FNP rate between valgus TKA with and without FNR (2.4% vs 2.1%) [18]. Therefore, the authors of this chapter do not recommend the routine use of FNR.…”
Section: The Fibular Nerve Dilemmamentioning
confidence: 85%
“…2 In a systematic review of the literature, Pujik et al assessed 27 studies that evaluated 1,397 valgus knees. 14 They found that the overall common peroneal nerve palsy rate was 1.9% after TKA for valgus deformity. They also found no significant differences in the nerve palsy rate between TKA with and without peroneal nerve release (2.4% vs. 2.1%), with lateral soft tissue release (2.2%) or with an osteotomy (0.4%).…”
Section: Complicationsmentioning
confidence: 98%
“…Tibial nerve becomes shallow to popliteal vessels and passes to the artery medial side at knee. In the distal popliteal fossa, two heads intersection of gastrocnemius covers it [14] .…”
Section: Tibial Nervementioning
confidence: 99%